Effectiveness of Fu’s subcutaneous needling combined with muscle energy technique for postpartum perineal pain: a randomized controlled trial - Shao, Yuchun; Lin, Zhanxiang; Shi, Yuan; He, Ling; Han, Dongmiao; Liu, Zicai (Frontiers in Medicine, 2025)
BackgroundPerineal pain after natural childbirth is a common problem among women after delivery, significantly impairing patients’ quality of life and increasing familial burden. This study evaluates the efficacy of Fu’s subcutaneous needling combined with muscle energy technique (FSN + MET) on perineal wound pain after natural childbirth.MethodsThis randomized controlled trial was conducted at Yuebei People’s Hospital. Seventy women experiencing perineal wound pain following spontaneous vaginal delivery in the hospital’s Obstetrics Department between January 2023 and December 2024 were enrolled. Participants were randomly assigned to either an intervention group or a control group (35 per group) using a random number table. The control group received conventional rehabilitation plus MET, while the intervention group received FSN in addition to conventional rehabilitation and MET. Pain improvement was assessed after 5 days of treatment.ResultsThe efficacy of FSN + MET was assessed using the Number Rating Scale (NRS), Activities of Daily Living (ADL), Fugl-Meyer Lower Limb Motor Function Score (FMA), Self-Rating Anxiety Scale (SAS), and satisfaction survey of treatment effect. Before treatment, there was no significant difference between the two groups regarding age, days of gestation, postpartum pain scores, NRS score, FMA lower limb score, ADL, SAS, and satisfaction (P > 0.05). Following treatment, the FSN + MET group showed significantly greater improvements in NRS, FMA, ADL, and SAS scores compared to the control group (P < 0.05). This demonstrates that FSN + MET is superior to conventional methods in alleviating perineal wound pain, improving mobility, enhancing quality of life, and reducing anxiety in patients after spontaneous delivery.ConclusionFSN + MET effectively reduces postpartum perineal pain and improves functional recovery.